The Role of Innate Lymphoid Cells in Cancer Development and Immunotherapy - Sugimura, Rio; Wang, Clement Yisai (Frontiers in Cell and Developmental Biology, 2022)
Innate Lymphoid Cells (ILCs) are an elusive type of innate immune cell that was only discovered recently. Their tissue residency and dependency makes them a niche group of cells that bridge the adaptive and innate immune system. The nomenclature and classification of ILCs have been challenging due to their heterogeneity. The currently agreed ILC classification splits the cells into two categories including cytotoxic and helper ILCs. The tumour microenvironment is often hostile for immune cells. Remodeling the microenvironment and regulating other immune cells - achieved by ILCs- can enhance anti-tumor effects. How ILCs regulate other immune cells in the tumor microenvironment remains to be understood. Here we review current understanding of the role of ILCs in the tumor microenvironment. ILCs recruit CD8 positive T and memory T cells in PDAC, ILCs are also able to help CD108 positive B cells migrate toward tumour locations. In NSCLC, ILC3s are seen helping resident macrophages enhancing the mucus immunity to cancer cells. We then highlight the roles of cytokines and immune checkpoint pathways in ILCs and its implication in immunotherapy.